Pielewin i pustka. Rzecz o nowych horyzontach literatury - Nakoneczny, Tomasz (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The prose of Victor Pelevin, one of the best-known contemporary Russian writers, is usually associated with postmodernism. Some interpreters believe, however, that the proper context for the discussion of Pelevin is not postmodernism, but the traditional Russian cultural categories. For the author of this article the more fruitful way is to search for a variety of traditional and modern sources of cultural inspiration (intertextuality), which helped to establish the new forms of communication between writer and reader in the works of Pelevin.